تقدير محددات الايراد العام للقطاع السياحي في الجزائر (El-Wahat Journal for Research and Studies, 2023)
ملخص:تهدف الدراسة إلى تقدير وتحليل العوامل المحددة لمردودية القطاع السياحي في الجزائر من خلال دراسة تحليلية وقياسية لبيانات سنوية للفترة (2000-2020)، حيث تم الاعتماد على نموذج الانحدار الذاتي للفجوات الموزعة المتباطئة (ARDL) في اختبار العلاقة بين متغيرات الدراسة، وقد خلصت الدراسة إلى وجود علاقة موجبة في الأجل الطويل والقصير في نفس الوقت بين كل من الايرادات السياحية من جهة وإجمالي الليالي السياحية وإجمالي السياح الوافدين من جهة أخرى، إضافة إلى علاقة عكسية في الأجلين بين الإيرادات السياحية وعدد العمالة السياحية.كلمات دالة: القطاع السياحي، الإيراد السياحي، العمالة السياحية، الليالي السياحية، السياحة.Abstract:The study aims to estimate and analyse the factors of profitability of the tourism sector in Algeria during the period through an econometric study of annual data for the period (2000-2020), The study employed Auto Regressive Distributed Lag (ARDL) to test the relationship among the variables. The findings of the study dictate there is a long/ short run relationship between the tourism revenues on the one hand and the total number of tourist nights and the total number of incoming tourists on the other hand, additionally, the study found a negative relationship between the tourism revenues and the tourist employment in both short and long-run.Key words: Tourism Sector, Tourism Revenue, Tourist employment, Tourist Nights, Tourism.